License to Kill? Domestic Cats Affect a Wide Range of Native Fauna in a Highly Biodiverse Mediterranean Country - Mori, Emiliano; Menchetti, Mattia; Camporesi, Alberto; Cavigioli, Luca; Tabarelli de Fatis, Karol; Girardello, Marco (Frontiers in Ecology and Evolution, 2019)
Amongst domestic animals, the domestic cat, Felis catus, is widely considered to be one of the most serious threats to wildlife conservation. This is particularly evident for island ecosystems, as data for mainland countries are often lacking. In Italy, the European country that is richest in biodiversity, cats are very popular pets. In this work, we aimed at assessing the potential spectrum of wild vertebrates that may be killed by free-ranging domestic cats, and we considered our results within the context of their conservation status and IUCN threat category. We collected data on the impact of cats both through a citizen science approach (wildlife predations by 145 cats belonging to 125 owners) and by following 21 of these 145 cats for 1 year and recording all of the prey they brought home. Domestic cats may kill at least 207 species (2042 predation events) in Italy; among those, 34 are listed as “Threatened” or “Near Threatened” by the IUCN and Italian Red Lists. Birds and mammals such as passerines and rodents were reported to be the groups most commonly killed by free-ranging cats. When considering this diet in functional trait space, we observed that the class occupying the largest functional space was that of birds, followed by mammals, reptiles, and amphibians. Thus, the largest impact was on the functional structure of mammal and bird communities. The use of a collar bell did not affect the predation rate of cats, and the number of prey items brought home decreased with increasing distance from the countryside. We provided strong evidence that free-ranging domestic cats may seriously affect the conservation of threatened and non-threatened wildlife species, which are already suffering from population declines due to other causes, e.g., habitat loss. The mitigation of the impacts of domestic cats on wildlife requires dissemination projects promoting responsible cat ownership, as well as a restriction of free-ranging behavior, particularly at nighttime.